2018
DOI: 10.15316/sjafs.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

41 B Asma Anacına In Vivo Kolhisin Uygulamalarının Morfolojik ve Sitolojik Etkileri

Abstract: Ekonomik olarak çok geniş bir alanda yapılan bağcılık, filoksera zararlısının geniş alanlara yayılması nedeniyle neredeyse anaç kullanılmadan yapılamaz hale gelmiştir. Mevcut asma anaçları sektörün gereksinimlerini tam olarak karşılayamadığından anaç ıslahı da süreklilik arz etmektedir. Bu maksatla vegetasyon süresi daha kısa, biyotik ve abiyotik stress koşullarına daha dayanıklı anaçların geliştirilmesine çalışılmaktadır. Bağcılıkta tetraploid üzüm çeşitlerinin yanısıra anaçların da geliştirilmesi son yıllard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
2
1
Order By: Relevance
“…Stomata area values were significantly differed due to the colchicine applications. A similar results of colchicine treatments was reported by Kara et al, (2018) on stomatal differences without genome doubling.…”
Section: Stomatal Density (Stomata MM -2 )supporting
confidence: 88%
“…Stomata area values were significantly differed due to the colchicine applications. A similar results of colchicine treatments was reported by Kara et al, (2018) on stomatal differences without genome doubling.…”
Section: Stomatal Density (Stomata MM -2 )supporting
confidence: 88%
“…This difference is probably due to increased cell size of polyploid plants (Marinho et al, 2014) and/or decreased leaf mesophyll space (Lundgren et al, 2019). Although the stomatal characteristics of the selected plants in our study were like the results of previous studies (Kara et al, 2018a;Zeng et al, 2019;Bae et al, 2020), ploidy could not be confirmed.…”
Section: Stoma Density (Number MM -2 ) and Stoma Sizes (μM)contrasting
confidence: 75%
“…In surviving plants, stomatal density per unit area (number mm -2 ) (Kara et al, 2018c), stomatal sizes (μm) (Kara et al, 2018a), chloroplast numbers in stoma guard cells (number stoma -1 ) (Kara et al, 2018a;Yazar, 2021), leaf thickness, chlorophyll content (Kara et al, 2018b) and Flow Cytometry (FC) analyzes (Yazar, 2018) were done. According to the results of all analysed data, the effects of oryzalin and N2O treatments on chromosome folding in grapevine were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…This difference is probably due to an increase in cell size in polyploid individuals (Marinho et al 2014) and/or a decrease in leaf mesophyll porosities (Lundgren et al 2019). The stomatal characteristics (Bae et al 2020, Kara et al 2018a, Zeng et al 2019 and chloroplast numbers (Ewald et al 2009, Rao et al 2019, Rêgo et al 2011 of polyploid plants obtained in this study were like previous studies, and our results confirmed previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The nuclear DNA content of the Vitaceae family was between 0.62 and 1.24 pg (Chu et al 2018), nine different diploid Vitis vinifera varieties ranged from 1.17 to 1.26 (Leal et al 2006), diploid Tekirdag Muscat and Michele Palieri varieties were 1.10 and 1.20 (Ergönül et al 2018), and diploid 41 B grapevine rootstocks were reported as 1.028 pg (Kara et al 2018a). Gordej et al (2019) reported that the nuclear DNA content of tetraploid plants obtained because of N 2 O application increased 1.7 to 1.82-fold compared to diploids.…”
Section: Discussionmentioning
confidence: 99%